Multivariate dynamics of one-mode and two-mode networks: Explaining similarity in sports participation among friends. (8th June 2018) - FUJIMOTO, KAYO; SNIJDERS, TOM A. B.; VALENTE, THOMAS W.
Abstract: We examined social mechanisms that account for similarity in the social context of school-sponsored extracurricular sports activities among friends. We distinguish two social mechanisms: "shared sports activities that lead to friendship, " whereby friendship formation and maintenance are conditioned by joint sports participation, and "friendship that leads to shared sports activities, " a form of social influence whereby adolescents join or maintain certain sports activities based on their friends' choices. Using a longitudinal sample of 1, 776 10th graders at five high schools in Southern California, we employed a stochastic actor-oriented multivariate dynamic model to model the dynamic interplay between the two-mode affiliation network of adolescents' participation in sports activities and the one-mode friendship network. As a corresponding descriptive method, we propose a quantitative measure for the relative strength of the two-mentioned mechanisms as explanations of the association between the one-mode and the two-mode network. Further, we introduce two specifications that represent homophily effects in the two-mode network and apply them to test gender homophily in sports participation. The results provide strong evidence for both mechanisms, with friendship leading to shared sport activities as stronger than shared sports activities leading to friendships in explaining adolescents' friendships with co-participants.